Implementasi Perjanjian Sewa Menyewa Tanah oleh PT. KAI kepada PT. Herona Express Pekalongan: Analisis Akad Ijarah - Hasna, Dewi; Suhendar, Heris; Budiman, Satria (el hisbah Journal of Islamic Economic Law, 2022)
Economic transactions are carried out by humans in order to fulfill their needs, one of which is a land lease agreement as carried out by PT. KAI with PT. Herona Express Pekalongan. What's interesting about this case, one of the parties changed the contents of the lease agreement, and the change in the agreement was in the lease period that had not yet expired. So it is interesting to study using ijarah contract analysis, is there a unilateral change in an agreement whether it is in accordance with the concept of ijarah contract. This research is a field research with a qualitative approach. The results of the study show that based on the results of the analysis, in general the land lease agreement has fulfilled its pillars and conditions. The change in the agreement does not damage the pillars and terms of the agreement because the change in agreement is based on the approval of the related parties, besides that the party that changed the agreement (PT. KAI Express) also provides compensation in the form of relocation. Meanwhile, when viewed from the reasons for changing the agreement which prioritizes the public interest, it is in line with the concept of maslahah 'ammah.